2007
DOI: 10.1007/s11145-007-9076-8
|View full text |Cite
|
Sign up to set email alerts
|

Word reading and reading comprehension: stability, overlap and independence

Abstract: Longitudinal twin data were analyzed to investigate the etiology of the stability of genetic and environmental influences on word reading and reading comprehension, as well as the stability of those influences on their relationship. Participating twin pairs were initially tested at a mean age of 10.3 years, and retested approximately five years later. Both word reading and comprehension were found to be highly stable, and genetic influences were primarily responsible for that stability. In contrast to studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 49 publications
(86 reference statements)
7
53
0
Order By: Relevance
“…The dual skills of word recognition and listening comprehension are recognized in the literature as the main components of reading competence, according to the Simple View of Reading (SVR; Aaron, Joshi, Gooden, & Bentum, 2008;Aaron, Joshi, & Williams, 1999;Betjemann et al, 2008;Gough & Tunmer, 1986). Although evidence supports this model, studies have also suggested that other skills may be integrated into the reading competency model, such as processing speed or fl uency in word recognition (Aaron et al, 2008;Aaron et al, 1999;Oakhill, Cain, & Bryant, 2003;Tilstra, McMaster, Van den Broek, Kendeou, & Rapp, 2009).…”
Section: Reading Competence: Strategies For Word Recognition and Compmentioning
confidence: 99%
“…The dual skills of word recognition and listening comprehension are recognized in the literature as the main components of reading competence, according to the Simple View of Reading (SVR; Aaron, Joshi, Gooden, & Bentum, 2008;Aaron, Joshi, & Williams, 1999;Betjemann et al, 2008;Gough & Tunmer, 1986). Although evidence supports this model, studies have also suggested that other skills may be integrated into the reading competency model, such as processing speed or fl uency in word recognition (Aaron et al, 2008;Aaron et al, 1999;Oakhill, Cain, & Bryant, 2003;Tilstra, McMaster, Van den Broek, Kendeou, & Rapp, 2009).…”
Section: Reading Competence: Strategies For Word Recognition and Compmentioning
confidence: 99%
“…Research with older children has previously explored the genetic and environmental relations between individual differences in word recognition, reading comprehension, and listening comprehension (Betjemann, Keenan, Olson, & DeFries, in press;Betjemann et al, 2008;Harlaar & Petrill, 2009;Keenan, Betjemann, Wadsworth, DeFries, & Olson, 2006). These studies have revealed correlated but also independent genetic influences on word recognition, reading comprehension, and listening comprehension.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…We also explored the developmental genetic and environmental correlations for vocabulary from pre-kindergarten through grades 2 and 4, and we compared the genetic and environmental correlations between vocabulary and the reading measures at each test occasion. Thus we were able to test hypotheses about developmental changes in the etiology of individual differences in vocabulary and of the relations between vocabulary, word recognition, decoding, and reading comprehension.Research with older children has previously explored the genetic and environmental relations between individual differences in word recognition, reading comprehension, and listening comprehension (Betjemann, Keenan, Olson, & DeFries, in press;Betjemann et al, 2008;Harlaar & Petrill, 2009;Keenan, Betjemann, Wadsworth, DeFries, & Olson, 2006). These studies have revealed correlated but also independent genetic influences on word recognition, reading comprehension, and listening comprehension.…”
mentioning
confidence: 99%
“…Support for the separate contribution that word recognition and comprehension have on reading ability came from genetic studies. Twin studies suggest that there is a separate genetic influence for word recognition and listening comprehension on reading ability (Keenan et al, 2006) and the genetic contribution of these two factors is stable over time (Betjemann et al, 2008). However, since reading is a learned skill, other cognitive and environmental elements are clearly involved (Byrne et al, 2009; Gayan & Olsen 2003 Petrill et al, 2006).…”
Section: Introductionmentioning
confidence: 99%